Development of Production Capacities in Agricultural Product Processing in the Urbanized Agglomeration Areas of the Astana by 2030 - BEKTLEEVA, Dina; GELASHVILI, Nikolay; SALZHANOVA, Zaure; TERZHANOVA, Aigul; ULYBYSHEV, Dmitriy (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
The relevance of the research problem is caused by the modern discourse of the production potential usage in the framework of food security. Thus, the aim of this study is to examine the production capacity of agricultural and food products processing within the Astana agglomeration. Data for analyzes were taken from the Agency on Statistics of the Republic of Kazakhstan, Department of the statistics on Astana city, statistical yearbooks on economic development of Kazakhstan regions, and ‘Kazakhstan-2050’ Strategy. The structure of the production capacities in the meat, dairy, milling and bakery industries of the selected region is presented. Appropriate proposals for the creation of new production capacities in the food industry were formed. The practical value is that the authors forecast food industry development up to 2030.